South Asia : Pension Schemes for the Formal Sector, Emerging Challenges and Opportunities for Reform - World Bank (Washington, DC, 2012)
For centuries informal arrangements such as intra-family transfers have been the primary source of old-age income support in South Asia. That remains true even today. Current patterns suggest that only around 1 in 10 of South Asia's half a billion workers will enter old age with a pension related to pre-retirement earnings. Pension schemes in South Asia cover small shares of the population, concentrated in the formal sector (table 1). Retirement income plans for the formal sector have for the most part performed poorly-both for their participants and for the economy. But while several countries in the region are exploring or already introducing reforms of civil service pension schemes, the performance of retirement income schemes available to the rest of the formal sector has received far less attention. The policy framework for most of these programs has barely changed since they were created, in some cases nearly half a century ago. Moreover, these schemes involve even more complex political economy issues, because governments have often used their funded (or partially funded) structures to address fiscal gaps. Now is a critical time to consider more broadly the problems affecting retirement income schemes for the formal sector. The two defined benefit programs in India and Pakistan, for example, have not yet matured. As time passes, future pension promises will become more deeply entrenched, making reform even more challenging. And as funded plans continue to grow, there is a risk of further misallocation of savings. Perhaps more important, there are encouraging signs of economic growth in the region and thus good possibilities for expanding the coverage of these programs. But even as a growing number of younger workers join the formal labor market and thus formal retirement schemes, urbanization is likely to weaken traditional informal arrangements for the elderly, including intra-family transfers. Strengthening retirement income schemes for the formal sector will help the region better prepare for the demographic change occurring over the next half century. This report seeks to provide a framework for improving the performance of pension schemes for the formal sector. After an introduction, Chapter 2 examines civil service pension schemes, chapter 3 focuses on mandatory private sector schemes, chapter 3 discusses the expansion of voluntary retirement savings arrangements, and chapter 5 is directed toward improving the business environment for retirement savings schemes. Chapter 6 presents conclusions.